Eu não sei falar direito, então eu erro a palavra: problematizando os desvios fonológicos no processo de alfabetização escolar - Staudt, Letícia Bello (Universidade do Vale do Rio dos Sinos, 2015)
This research presents reflections about the incidence of phonological disorders in children’s speech in the literacy process, and its relation to the acquisition of writing, showing the importance of the phonological awareness stimulation for overcoming the phonological difficulties. The study was developed in two public schools in the metropolitan area of Porto Alegre. It was followed twelve informants, divided into two groups: monitoring and intervention. The monitoring group, consisting on four respondents, aged between 8 and 11 years old, were followed for one year, but not receiving any kind of intervention. The intervention group, however, was made up of eight children, between 6 and 8 years old. For this group, it was developed a dice game, entitled Fonodado, which promoted the use of phonemes and missing syllabic structure in the children’s phonetic inventory through activities that encouraged phonological awareness and writing. Children participated in the activity weekly in individual sessions that lasted thirty minutes for about two months. As a result, it was observed positive effects in the post-testing of the intervention group regarding the development of phonological awareness level tested by CONFIAS, beyond overcoming all or part of the phonological disorders observed in the informants’ speech. Similarly, children in the intervention group showed development of writing, overcoming difficulties caused by phonological nature in the spelling of words. In contrast, individuals in the monitoring group remained almost all the phonological disorders observed at baseline, as well as difficulties in the written form of the language. The research also aimed to reflect on the use of the phonological disorder term, bringing considerations about the implications of using this term in the identification of children with such speech characteristics, considering aspects related to the inclusion of these students in the school environment. Thus, it proposes a change in the way the speech disorder is understood and in its implication toward the child’s development, which depends, among other factors, on the attention given by the educator to the students’ linguistic manifestations and on diversifying the teaching practice, searching for alternatives to the learning of all.
Keywords: Desvios fonológicos; Fonologia; Consciência fonológica; Aprendizagem da escrita; Ensino fundamental; Inclusão; Phonological disorders phonology; Phonological awareness; Literacy; Elementary school; Inclusion; ACCNPQ::Lingüística, Letras e Artes::Lingüística